Relationship between flat foot deformity, Q angle and knee pain - Amir Letafatkar; Shahrzad Zandi; Majid Khodaei; Jafar Belali Voshmesara; Maryam Mazidi (Vesnu Publications, 2012)
Introduction: Based on Janda's theory of kinetic chain, dysfunction in one joint can affect other joints of body. The aim of the present study was to determine the relationship between flat foot deformities, Q angle and knee pain in Iranian freestyle wrestlers. Materials and Methods: Twenty freestyle wrestlers (mean age, 19.11±0.86 years; mean weight, 70.5 ± 18.4 kg; and mean height, 173.2 ± 9.1 cm) were recruited from Iranian national team. Navicular Drop (with Brody method), Goniometer, and either pain score or visual analogue scale (VAS) were respectively used for the assessment of flat foot, Q angle and knee pain measurement. Pearson correlation coefficient test was conducted for statistical analysis of data using SPSS software version 18. Significance level was set at P ≤ 0.05. Also Inter Class Correlation Coefficient (ICC) used to evaluate the repeatability of measurements. Results: Results indicated that there was significant relationship between flat foot deformity and knee pain in freestyle wrestlers (r = 0.686). Although Increased Q angle and knee pain had a significant correlation in dominant leg (r = 0.949), there was a weakly significant relationship between Increased Q angle and flat foot deformity in dominant leg (r = 0.278). Conclusion: Considering the present study's results and based on kinetic chain theory, flat foot deformity may result in patella lateral rotation and increase of Q angle which, in turn, may eventually cause knee pain. Keywords: Kinetic chain theory, Knee pain, Flat foot deformity